Efficacy of anakinra in active ankylosing spondylitis: a clinical and magnetic resonance imaging study. Issue 9 (5th April 2004) - Tan, A L; Marzo-Ortega, H; O'Connor, P; Fraser, A; Emery, P; McGonagle, D
Abstract : Objective: To determine the efficacy of anakinra, an interleukin 1 receptor antagonist in active ankylosing spondylitis (AS), and to investigate the effect of anakinra treatment on spinal enthesitis/osteitis using magnetic resonance imaging (MRI). Methods: A 3 month open label study of anakinra (100 mg subcutaneous injection daily) was carried out in nine patients with active AS who had back pain and an increased acute phase response, and who had failed to respond to at least one non-steroidal anti-inflammatory drug. Clinical assessment included the Bath AS Functional Index (BASFI), Bath AS Disease Activity Index (BASDAI), and AS Quality of Life (ASQoL) before and after treatment. Fat suppressed MRI of the spine and sacroiliac joints was performed with a 1.5 T scanner at baseline and at 3 months to determine the effect of treatment on spinal enthesitis/osteitis. Results: Significant improvement was found in the BASFI (median baseline 5.88, 3 months 3.63, p = 0.021), BASDAI (median baseline 5.63, 3 months 3.48, p = 0.028), ASQoL (median baseline 12, 3 months 8, p = 0.011) and laboratory measures reflecting inflammation, with C reactive protein (median baseline 31 mg/l, 3 months 17 mg/l, p = 0.036) and erythrocyte sedimentation rate (median baseline 19 mm/1st h, 3 months 15 mm/1st h, p = 0.008) also showing significant improvement. Six patients (67%) achieved the Assessments in AS (ASAS) Working Group criteria of 20% improvement. Of the 38 regions of enthesitis/osteitis determined by MRI at baseline, 23 (61%) either improved or regressed completely. Conclusions: This open label pilot study suggests that anakinra is effective in controlling the clinical manifestations of AS. The clinical response was reflected by an improvement in MRI determined spinal enthesitis/osteitis.